Modeling of Metalized Food Packaging Plastics Pyrolysis Kinetics Using an Independent Parallel Reactions Kinetic Model - Samy Yousef (Polymers, 2020)
Recently, a pyrolysis process has been adapted as an emerging technology to convert metalized food packaging plastics waste (MFPWs) into energy products with a high economic benefit. In order to upscale this technology, the knowledge of the pyrolysis kinetic of MFPWs is needed and studying these parameters using free methods is not sufficient to describe the last stages of pyrolysis. For a better understanding of MFPWs pyrolysis kinetics, independent parallel reactions (IPR) kinetic model and its modification model (MIPR) were used in the present research to describe the kinetic parameters of MFPWs pyrolysis at different heating rates (5–30 °C min−1). The IPR and MIPR models were built according to thermogravimetric (TG)-Fourier-transform infrared spectroscopy (FTIR)-gas chromatography−mass spectrometry (GC-MS) results of three different types of MFPWs (coffee, chips, and chocolate) and their mixture. The accuracy of the developed kinetic models was evaluated by comparing the conformity of the DTG experimental results to the data calculated using IPR and MIPR models. The results showed that the dependence of the pre-exponential factor on the heating rate (as in the case of MIPR model) led to better conformity results with high predictability of kinetic parameters with an average deviation of 2.35% (with an improvement of 73%, when compared to the IPR model). Additionally, the values of activation energy and pre-exponential factor were calculated using the MIPR model and estimated at 294 kJ mol−1 and 5.77 × 1017 kJ mol−1 (for the mixed MFPW sample), respectively. Finally, GC-MS results illustrated that pentane (13.8%) and 2,4-dimethyl-1-heptene isopropylcyclobutane (44.31%) represent the main compounds in the released volatile products at the maximum decomposition temperature.